Análise da trajetória de poços horizontais em reservatório de óleo pesado - Brito, Eduardo Eudes Farias de (2008)
The application of thermal methods, to increase the recovery of heavy oil in mature fields through drainage with multilateral and horizontal wells, has been thoroughly studied, theorically, experimentally, testing new tools and methods. The continuous injection of steam, through a steam injector well and a horizontal producer well in order to improve horizontal sweep of the fluid reservoir, it is an efficient method. Starting from an heterogeneous model, geologically characterized, modeling geostatistics, set history and identification of the best path of permeability, with seismic 3D, has been dubbed a studying model. It was studied horizontal wells in various directions in relation to the steam and the channel of higher permeability, in eight different depths. Into in the same area were studied, the sensitivity of the trajectories of horizontal wells, according to the depth of navigation. With the purpose of obtaining the highest output of oil to a particular flow, quality, temperature and time for the injection of steam. The wells studied showed a significant improvement in the cumulative oil recovery in one of the paths by promoting an alternative to application in mature fields or under development fields with heavy oil